The awakening course the secret to solving all problems - Vitale, Joe 1953- (Wiley, 2011)
The author presents a program explaining the four stages of awakening. He offers a step-by-step approach for finding and achieving one's goals and desires, as well as a path to complete mind, body, and spiritual transformation.
Includes bibliographical references (pages 216-222) and index. - Print version record
Keywords: Success; Wakefulness; Transcendence (Philosophy); Life skills; Succès; Veille; Transcendance (Philosophie); Habiletés de base; SELF-HELP; Personal Growth; Success; SELF-HELP; Personal Growth; Happiness; SELF-HELP; Personal Growth; General; PSYCHOLOGY; Applied Psychology